Comparative analysis of design models for concrete corbels - Araújo,D. L. (2016)
ABSTRACT The main objective of this paper is performing a comparative analysis of some design models for precast concrete corbels. For this, it was analyzed design models from Brazilian (NBR 9062) and European (EUROCODE 2) Codes and a US design handbook (PCI). Moreover, three analytical models showed in the literature are analyzed. The objective of this comparative is identifying the best design models to represent the failure load of concrete corbels by the tie yields or by the concrete crushing. Moreover, it is intended to evaluate the contribution of horizontal stirrups to resistance of concrete corbels. For this, a database was assembled from test results of concrete corbels carried out by several researchers and they are showed in the literature. The design models were applied to this database and from statistical tools, adjustments coefficients are recommended to be applied on these design models to take into account the results dispersion found in the analysis.